2021
DOI: 10.1175/jcli-d-20-0377.1
|View full text |Cite
|
Sign up to set email alerts
|

Intraseasonal Soil Moisture–Atmosphere Feedbacks on the Tibetan Plateau Circulation

Abstract: Substantial intraseasonal precipitation variability is observed across the Tibetan Plateau (TP) during boreal summer associated with the subtropical jet location and the Silk Road pattern. Weather station data and satellite observations highlight a sensitivity of soil moisture and surface fluxes to this variability. During rain-free periods of two or more days, skin temperatures are shown to rise as the surface dries, signalling decreased evaporative fraction. Surface fluxes are further enhanced by relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…The systems that made the greatest contributions to precipitation > $ > $5 mm hr −1 over the TP (including both MCSs and TCSs) were located in the eastern part of the TP. This regional pattern may be related to surface properties, such as soil moisture and vegetation, which can regulate heat fluxes in the boundary layer (Talib et al., 2021) and thereby increase the convective instability at higher altitudes. This has, for instance, been suggested by Sugimoto and Ueno (2012) who found that soil moisture played a crucial role for convection initiation over the eastern TP.…”
Section: Discussionmentioning
confidence: 99%
“…The systems that made the greatest contributions to precipitation > $ > $5 mm hr −1 over the TP (including both MCSs and TCSs) were located in the eastern part of the TP. This regional pattern may be related to surface properties, such as soil moisture and vegetation, which can regulate heat fluxes in the boundary layer (Talib et al., 2021) and thereby increase the convective instability at higher altitudes. This has, for instance, been suggested by Sugimoto and Ueno (2012) who found that soil moisture played a crucial role for convection initiation over the eastern TP.…”
Section: Discussionmentioning
confidence: 99%
“…The stronger vegetation response to precipitation is expected to dominate any weaker impacts in the opposing direction. Moreover, the impact of intraseasonal surface variability on precipitation may be non-local (Chug & Dominguez, 2019;Talib et al, 2021Talib et al, , 2022. Water controls on transpiration (rather than direct evaporation) provide the dominant pathway for atmospheric feedbacks on these timescales.…”
Section: Discussionmentioning
confidence: 99%
“…(2005) who showed that West African monsoon winds maximise overnight when the convective boundary layer is diminished and boundary‐layer turbulence is weak. The diurnally varying atmospheric response is similar to those found in modelling (Rácz and Smith, 1999; Smith and Spengler, 2011) and observational (Hoinka and Castro, 2003; Parker et al ., 2005; Howard and Washington, 2018; Talib et al ., 2021) studies of the dynamical atmospheric response to surface warming in the Sahel and other regions of the world. The southward monsoon shift also leads to substantial humidity perturbations with specific humidity decreasing by up to 1.6 g·$$ \cdotp $$kgprefix−1$$ {}^{-1} $$ to the north of maximum warming (Figure 7h).…”
Section: Intraseasonal Soil Moisture– Atmosphere Feedbacksmentioning
confidence: 99%